Acanthopanax senticosus total flavonoids alleviate lipopolysaccharide-induced intestinal inflammation and modulate the gut microbiota in mice. Issue 2 (25th February 2022) - Wang, Xiaoya; Zhang, Xinyu; Su, Jianqing; Chu, Xiuling
Abstract: Here, we study the therapeutic effect of Acanthopanax senticosus total flavonoids (ASTFs) using a mouse intestinal inflammation model. The inflammation model used in the present study was developed through lipopolysaccharide (LPS) treatment of mice. The experimental mice were divided into a control group, model group (10 mg/kg LPS), dexamethasone group (1 mg/kg DEX) and ASTF low-, medium- and high-dosage groups (200, 400 and 800 mg/kg, respectively). The morphological and structural changes in the ileum, jejunum and duodenum were observed using HE staining. The number of intestinal goblet cells (GCs) was calculated based on PAS staining. The contents of interleukin (IL)-1β, IL-6, prostaglandin E2 (PGE2) and tumor necrosis factor α (TNF-α) were determined using enzyme-linked immunosorbent assay (ELISA) and the related mRNA expression level were measured by RT-PCR. The protein expression levels of Toll-like receptor 4 (TLR4), MyD88, p65 and p-p65 were measured using Western blotting. In addition, the 16S rRNA sequences of bacterial taxa were amplified and analyzed to assess changes in the intestinal microbes of LPS-induced mice and also in response to regulation by ASTF. Following intervention with ASTF, different therapeutic effects were shown according to the various dosages tested, all of which resulted in improved intestinal morphology and an increased number of intestinal GCs, while the contents of IL-1β, IL-6, PGE2 and TNF-α and the related mRNA expression level were significantly reduced. The TLR4, MyD88 and p-p65/p-65 protein expression levels were also significantly reduced. In addition, 16S rRNA sequencing results show that LPS disrupts the structure of mouse gut microbes, though we observed that normal microbial status can be restored through ASTF intervention.